Challenges of prehospital emergency staff in the COVID-19 pandemic: A phenomenological research - Mohammad Mohammadi; Abdolghani Abdollahimohammad; Mohammadreza Firouzkouhi; Maryam Shivanpour (Journal of Emergency Practice and Trauma, 2022)
Objective: Pre-hospital emergency staff are involved in the front line of care for COVID-19 patients and face many challenges. The aim of this study was to explore the challenges of prehospital emergency staff in the COVID-19 pandemic. Methods: This qualitative research was conducted with a descriptive phenomenological approach. Purposeful sampling was applied and data collection was done through semi-structured interviews. Participants consisted of 16 pre-hospital emergency staff. Data analysis was performed using the Colaizzi approach. Results: Data analysis revealed five main themes including safety against COVID-19, knowledge deficit, fear and worry, challenges of transporting patients to the hospital, and selflessness. Conclusion: Pre-hospital emergency staff face many problems in personal, professional, equipment and cultural fields in the COVID-19 epidemic. In this regard, special attention from health systems is mandatory.